Methods of designing Arabic calligraphy vacations (Journal of the College of Basic Education, 2022)
Arabic calligraphy is of great importance in the Arab-Islamic civilization, as it is an effective means of communication and has a record of the history of nations and heritage, and through it the world learned about Arab thought and Islamic civilization. With the pen, he taught man what he did not know (Al-Alaq 3). The art of Arabic calligraphy is considered one of the huge and distinctive productions in the history of Islamic arts through the high ranks it reached, so that it acquired the significance of Islam and became a symbol of it, according to what was associated with it and its function in the line of Quranic texts, as this feature constituted a strong incentive in Striving to develop it and the emergence of calligraphic paintings is one of the products of this continuous endeavor.